Pertanggungjawaban Pidana Terhadap Pelaku Pencurian dengan Pemberatan : (Studi Kasus Putusan Nomor 1382/Pid.B/2023/PN Mdn) - Maniar Nainggolan; Endhita Putri; Putri Jesika; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The aim of this research is to find out how criminal responsibility is for perpetrators of theft with weights in the Legal Area of ​​the Medan District Court. The research method used is a normative legal method with a type of normative juridical research, where research focuses on studying the application of rules or norms in positive law. The results of this research show that the criminal and his partner were legally proven and promised to be guilty of committing the crime of "aggravated theft", the factor that caused the perpetrator to commit the crime of theft was because the criminal was addicted to drugs. The judge's decision stated that the fraudster did not find anything that could eliminate criminal liability for himself. Criminal liability for the defendant is imprisonment for: 10 (ten) months in prison minus the period of isolation that has been served and with an order that the defendant remain in detention.